ELECTORAL GOVERNANCE IN ZANZIBAR: A COMPREHENSIVE ANALYSIS OF POWERSHARING DYNAMICS AND CONFLICT MANAGEMENT - Mwinyi, Fatima Saidi; Kimaro, Joseph Elias (International Journal of Political Science and International Relations (IJPSIR), 2024)
Zanzibar, since the reinstatement of its multiparty system in 1992, has grappled with a recurrent wave of election-related turmoil, characterized by a disconcerting frequency of killings, injuries, and societal unrest. This abstract endeavors to provide an in-depth exploration of the intricate dynamics underlying the tumultuous electoral landscape in Zanzibar, shedding light on the pervasive mistrust, accusations, and challenges that have marred each election cycle. Citing John (2020) and the insights of Minde et al. (2018), the narrative unfolds against a backdrop of unadjusted electoral practices within the multiparty system, attributing the recurring tragedy to systemic shortcomings. The competing political entities in Zanzibar’s elections, comprising both incumbent and opposition parties, find themselves ensnared in a cycle of mutual accusations, further exacerbated by a pervasive questioning of the electoral process itself. This perpetuated mistrust becomes the breeding ground for calls to secure a free and fair electoral process, invoking both soft and hard power. The abstract accentuates the consequential impact of this mistrust on Zanzibar’s political landscape, which becomes overwhelmingly dominated by electoral violence. The oscillation between demands for electoral transparency and the visceral contestation of election outcomes paints a vivid picture of the underlying tensions. By elucidating the multifaceted interplay of mistrust, accusations, and demands for electoral integrity, this research aims to contribute to a nuanced understanding of the complex challenges faced by Zanzibar in fostering a stable and democratic political environment. As Zanzibar continues to grapple with the persistent specter of electoral violence, the abstract lays the groundwork for future investigations into potential mechanisms for conflict resolution, institution-building, and the cultivation of an electoral culture grounded in trust and transparency.